Network-wide effects of pallidal deep brain stimulation normalised abnormal cerebellar cortical activity in the dystonic animal model - Fabiana Santana Kragelund; Konstantinos Spiliotis; Marco Heerdegen; Tina Sellmann; Henning Bathel; Anika Lüttig; Angelika Richter; Jens Starke; Rüdiger Köhling; Denise Franz (Neurobiology of Disease)
Background: Deep brain stimulation (DBS) targeting globus pallidus internus (GPi) is a recognised therapy for drug-refractory dystonia. However, the mechanisms underlying this effect are not fully understood. This study explores how pallidal DBS alters spatiotemporal pattern formation of neuronal dynamics within the cerebellar cortex in a dystonic animal model, the dtsz hamster. Methods: We conducted in vitro analysis using a high-density microelectrode array (HD-MEA) in the cerebellar cortex. For investigating the spatiotemporal pattern, mean firing rates (MFR), interspike intervals (ISI), spike amplitudes, and cerebellar connectivity among healthy control hamsters, dystonic dtsz hamsters, DBS- and sham-DBS-treated dtsz hamsters were analysed. A nonlinear data-driven method characterised the low-dimensional representation of the patterns in MEA data. Results: Our HD-MEA recordings revealed reduced MFR and spike amplitudes in the dtsz hamsters compared to healthy controls. Pallidal DBS induced network-wide effects, normalising MFR, spike amplitudes, and connectivity measures in hamsters, thereby countervailing these electrophysiological abnormalities. Additionally, network analysis showed neural activity patterns organised into communities, with higher connectivity in both healthy and DBS groups compared to dtsz. Conclusions: These findings suggest that pallidal DBS exerts some of its therapeutic effects on dystonia by normalising neuronal activity within the cerebellar cortex. Our findings of reduced MFR and spike amplitudes in the dtsz hamsters could be a hint of a decrease in neuronal fibres and synaptic plasticity. Treatment with pallidal DBS led to cerebellar cortical activity similar to healthy controls, displaying the network-wide impact of local stimulation.